Antiglycine-receptor encephalomyelitis with rigidity. Issue 12 (10th December 2010) - Mas, Natalia; Saiz, Albert; Leite, Maria Isabel; Waters, Patrick; Baron, Manuel; Castaño, Dolores; Sabater, Lidia; Vincent, Angela; Graus, Francesc
Abstract : Background: Glycine receptor antibodies (GlyR-ab) were reported in a patient with progressive encephalomyelitis with rigidity and myoclonus (PERM). Methods: Three additional patients were clinically described. GlyR-ab was detected with a cell-based assay of HEK293 cells transfected with the α1 subunit of the GyR. Results: A 33-year-old woman presented with diplopia, dysphagia and gait ataxia that improved in 5 weeks. Then, she developed a typical stiff-person syndrome (SPS) that resolved with corticosteroids, but relapsed 17 months later with a stiff limb syndrome. After treatment with intravenous immunoglobulins (IVIG), she has been asymptomatic for 8 years. A 60-year-old man developed, dysphagia, diplopia, left facial palsy and right trigeminal hypoaesthesia in a few days, followed by muscular rigidity, corticospinal signs, myoclonic jerks and severe dysautonomia. He developed seizures and suffered a cardiac arrest that left him in a persistent vegetative state. A 48-year-old man presented with leg rigidity and frequent spells of trismus, muscle spasms followed by opisthotonus and diaphoresis. The symptoms were antedated by pruritus of the left scapulae, right arm and T11–T12 dermatome. At the same time he became progressively more aggressive with emotional irritability. He also developed dysgeusia (metallic taste) and severe concurrent behavioural changes and diurnal hypersomnia. Only the rigidity and the spasms improved after therapy. Conclusions: The clinical picture associated with GlyR-ab is wider than the classical view of PERM. GlyR-ab should be examined in patients with core symptoms of muscle rigidity and spasms atypical for SPS.